THE INFLUENCE OF TEACHER’S INSTRUCTIONAL OBJECTIVES ON VARIATIONS OF EXCHANGE PATTERNS IN AN EFL CLASSROOM - Maolida, Elis Homsini (Indonesian Journal of Applied Linguistics, 2013)
Abstract: This study investigates how teacher’s instructional objectives influence the variations of exchange pattern between teacher and students in their classroom interaction. The present paper tries to find out the variations of exchange pattern in teacher-students interaction and to observe how the teacher’s instructional objectives influence those variations. The data were obtained from 90 minutes observation and recording of classroom interaction between a pre-service teacher and her students, interview with the teacher, and document analysis. The findings show that the use of exchange patterns in teacher-students interaction varied across learning activities. An exchange pattern dominates a learning activity more than the other. In this case, teacher’s instructional objectives provide contexts that guide the teacher to manage the interaction so expected exchanges occur in the class. In other words, the instructional objectives create instructional activities that determine certain exchange patterns to occur through certain methods and strategies. The objectives also influence teacher’s strategies in initiating the exchanges, for example in questioning strategies. The domination of non anomalous and synoptic pattern indicates that instructional objectives help the teacher in creating a relatively more manageable interaction in the class. However, it also indicates that the objectives, to certain extent, impede the teacher’s initiation in expanding the interaction. This study is expected to raise teachers’ awareness to improve their educational planning such as lesson plan and consider some possible negative effects of relying too much on lesson plans. It can also be a reflective description for researchers to put learning objectives into consideration when they analyze classroom interaction.Keywords: instructional objectives, exchange patterns, interaction, lesson plan.